Introduction to the physical and biological oceanography of shelf seas - Simpson, John (John H.); Sharples, Jonathan (Cambridge ; New York : Cambridge University Press, 2012)
"In this exciting and innovative textbook, two leading oceanographers bring together the fundamental physics and biology of the coastal ocean in a quantitative but accessible way for undergraduate and graduate students. Shelf sea processes are comprehensively explained from first principles using an integrated approach to oceanography that helps build a clear understanding of how shelf sea physics underpins key biological processes in these environmentally sensitive regions. Using many observational and model examples, worked problems and software tools, the authors explain the range of physical controls on primary biological production and shelf sea ecosystems. Boxes throughout the book present extra detail for each topic and non-mathematical summary points are provided for physics sections, allowing students to develop an intuitive understanding. The book is fully supported by extensive online materials, including worked solutions to end-of-chapter exercises, additional homework/exam problems with solutions and simple MATLAB and FORTRAN models for running simulations"--
Machine generated contents note: Preface; 1. Introduction to the shelf seas; 2. Physical forcing of the shelf seas: what drives the motion of ocean?; 3. Response to forcing: the governing equations and some basic solutions; 4. Waves, turbulent motions and mixing; 5. Life in the shelf seas; 6. Seasonal stratification and the spring bloom; 7. Interior mixing and phytoplankton survival in stratified environments; 8. Tidal mixing fronts: their location, dynamics and biological significance; 9. Regions of freshwater influence (ROFIs); 10. The shelf edge system; 11. Future challenges in shelf seas; References; Index.
Includes bibliographical references and index.
Keywords: Oceanography; Coasts; Continental shelf; SCIENCE / Earth Sciences / Oceanography